Pengembangan media pembelajaran web google sites dalam pembelajaran IPAS pada siswa kelas IV SD Jurugentong - Kusumawardani, Yuliana Dwi; Utaminingsih, Retno (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2024)
This research aims to: 1) Find out the characteristics of Google Sites Web-based learning media in Class IV science and science learning at Jurugentong State Elementary School, Yogyakarta; 2) Knowing the suitability of Google Sites Web-based learning media in learning Elastic Objects for Class IV students at Jurugentong State Elementary School, Yogyakarta; 3) Knowing students' responses to Google Sites Web-based learning media in science and science learning in Class IV of Jurugentong State Elementary School, Yogyakarta. This research is research and development (R&D) with the ADDIE development model which consists of the Analysis, Design, Development, Implementation and Evaluation stages. The development media is a web. Media suitability assessments are carried out by media experts, material experts, and class IV teachers. The instruments used were questionnaires, interviews and documentation. Data analysis techniques use qualitative descriptive analysis and quantitative descriptive analysis. The research results show that: 1) This research produces Google Sites Web learning media which was developed with 4 characteristics, namely: learning media is displayed attractively, in accordance with learning objectives, uses language that is easy to understand, and can convey information; 2) Learning media is very suitable for use based on validation from media experts who obtained a score of 95.7% in the very appropriate category, the results of the assessment by material experts obtained a score of 100% in the very appropriate category, and the results of the assessment by the Class IV teacher obtained a score of 93.8% with very worthy category. The feasibility of Google Sites Web-based learning media was averaged with a score of 96.5% in the very feasible category; 3) The test results of student responses to Google Sites Web-based learning media include student response questionnaires with a score of 91.6% in the very good response category.